2020
DOI: 10.1111/rec.13156
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance is more important than seeding or grazing in determining soil microbial communities in a semiarid grassland

Abstract: A primary goal of ecological restoration is often to return processes and functions to degraded ecosystems. Soil, while often ignored in restoration, supports diverse communities of organisms and is a fundamental actor in providing ecosystem processes and services. We investigated the impact of seeding and livestock grazing on plant communities, soil microorganisms, and soil fertility 3 years after the restoration of a disturbed pipeline corridor in southeastern Arizona. The initial soil disturbance and topsoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…Thus, 1 year after planting, we can infer that plant and soil diversity were largely decoupled. Previous research has also observed a similar weak connection between plant and soil microbial diversity (Farrell et al., 2020; Prober et al., 2015; Tedersoo et al., 2014).…”
Section: Discussionsupporting
confidence: 52%
“…Thus, 1 year after planting, we can infer that plant and soil diversity were largely decoupled. Previous research has also observed a similar weak connection between plant and soil microbial diversity (Farrell et al., 2020; Prober et al., 2015; Tedersoo et al., 2014).…”
Section: Discussionsupporting
confidence: 52%
“…The reduction of compaction has been associated with increased infiltration and increased plant growth (Kozlowski 1999) although this affect is likely confounded with the effect of increasing herbaceous cover increasing infiltration similar to Thurow et al (1988). Examining the same pipeline restoration site, Farrell et al (2020) found that the topsoil treatment caused changes to the soil microbial communities and soil fertility, which was more influential in determining plant communities than seeding. Soil attributes (such as infiltration capacity, soil bulk density [i.e., compaction], soil structure, or soil organic matter) at a dryland restoration site may be a better early indicator of site recovery and productivity following a disturbance than the plant communities themselves (Costantini et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Farrell et al (2020) observed that soil microbial communities were more closely related to total plant cover, soil organic matter, and pH than seeding in a semi‐arid grassland of the southwestern United States. Farrell et al (2020) concluded that separating and maintaining the topsoil during a disturbance for a short period of time (2 months in their case) maintained soil conditions adequate for natural revegetation of plants recruited from adjacent areas or the soil seed bank.…”
Section: Impacts Of Ecosystem‐specific Restoration Activities On Soilmentioning
confidence: 86%
“…In a coastal dune system, Parson et al (2020) studied the impact of invasive species control as a restoration intervention and showed a strong legacy effect in soil microbial communities 5–10 years after invasive species treatment, both for soil microbial functional groups and for richness. The results of Parson et al (2020) and Farrell et al (2020) point to the importance of soil containing functional groups of microbes necessary for establishing desirable plant species (e.g. nitrogen‐fixing bacteria or mutualistic arbuscular mycorrhizal fungi).…”
Section: Impacts Of Ecosystem‐specific Restoration Activities On Soilmentioning
confidence: 99%